Healthcare Workers Experiences and Challenges during Sample Collection for COVID 19 in the Selected Institutionalized Quarantine Centers, Kathmandu - Thapa, Mamta; Maharjan, Bijay (Journal of Karnali Academy of Health Sciences, 2022)
Background: The frontline healthcare workers are progressively being involved in the COVID-19 crisis. Their role has been significant and made a crucial contribution, but they face many challenges along. The experiences and challenges of the frontline healthcare workers during sample collection remain unexplored. So, the researcher felt necessary to realize insights into the lived experiences of healthcare workers. The target of the study is to explain the fieldwork of the sample collection within the institutionalized quarantine of COVID-19 and explore the most important challenges and issues during sample collection.Methods: A qualitative case study methodology was adopted to describe swab collection events in the institutionalized quarantine of Kathmandu. Direct observation and field notes were kept based on descriptive information and informal communication with team members during swab collection. Telephone interviews with the team members were conducted at a convenient time.Results: Despite the fear of infection experienced by healthcare workers, they are ready to serve people, fulfilled responsibilities, concentrated on duties, and showed professionalism. They felt difficulty in working with airtight PPE and maintaining infection control measures for long working hours.Conclusion: The training on infection control measures and swab collection associated with COVID-19 helped to extend knowledge and develop confidence in skills. Furthermore, it is essential to supply adequate PPEs and ensure a secure working environment to cut back fear and uncertainty.